2022
DOI: 10.37360/blacpma.22.21.6.44
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnological potential of essential oils from different chemotypes of Lippia alba (Mill.) N.E.Br. ex Britton & P. Wilson

Abstract: This study reports the biotechnological importance of seven Lippia albaspecimens collected in different places in Brazil, and evaluation of some activities as larvicidal against Aedesspp., antifungal against dermatophytes; cytotoxicity against SNB-19 (astrocytoma), HCT-116 (human colon) and PC-3 (human prostate) cancer cell lines, and inhibition of the enzyme acetylcholinesterase (AChE).The essential oils, whose extraction yield was about 1.24 w/w ± 0.9%, showed differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The EO evaluated in this study consists mainly of citral (45.86%, geranial and neral being the two isomers of citral) and geraniol (14%). The chemotypes of L. alba EOs, which can be associated with the genetic forms of the plant species, have been characterised according to their main compounds, the variability of which can be related to the morphological characteristics of the leaves and the localities or environmental conditions of production 29 , 53 59 . Hennebelle et al 53 classified the EOs of L. alba into seven chemotypes on the basis of the phytochemical profiles of 4 samples from the French overseas departments and those of 54 other samples reported in 35 publications.…”
Section: Discussionmentioning
confidence: 99%
“…The EO evaluated in this study consists mainly of citral (45.86%, geranial and neral being the two isomers of citral) and geraniol (14%). The chemotypes of L. alba EOs, which can be associated with the genetic forms of the plant species, have been characterised according to their main compounds, the variability of which can be related to the morphological characteristics of the leaves and the localities or environmental conditions of production 29 , 53 59 . Hennebelle et al 53 classified the EOs of L. alba into seven chemotypes on the basis of the phytochemical profiles of 4 samples from the French overseas departments and those of 54 other samples reported in 35 publications.…”
Section: Discussionmentioning
confidence: 99%
“…The essential oil evaluated in this study consists mainly of citral (45.86%, geranial and neral being the two isomers of citral) and geraniol (14%). The chemotypes of L. alba EOs, which can be associated with the genetic forms of the plant species, have been characterised according to their main compounds, the variability of which can be related to the morphological characteristics of the leaves and the localities or environmental conditions of production [29,49,50,51,52,53,54,55]. Hennebelle et al [49] classi ed the essential oils of L. alba into seven chemotypes on the basis of the phytochemical pro les of 4 samples from the French overseas departments and those of 54 other samples reported in 35 publications.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, Lippia alba and Petiveria alliacea, belonging, respectively, to the Verbenaceae and Petiveriaceae families and native to Latin America, have gained prominence for their numerous medicinal benefits, particularly their anti-carcinogenic properties. Several studies have examined the anti-carcinogenic effects of their essential oils, in the case of L. alba, research has shown its potential in halting the cell cycle and inducing apoptosis in liver and lung cancer cells [14], colon and prostate cancer cells [15], leukemia cells [16], and gastric carcinoma cells [17]. Similarly, P. alliacea has been found to trigger cell apoptosis and reduce the growth capability of breast cancer cell colonies [18], along with diminishing tumor burden and myeloid leukemia metastasis [19].…”
Section: Introductionmentioning
confidence: 99%